Comparing the Profile Characteristics for Evaluation of the Effectiveness of the Agri-business Incubators (Indian Journal of Extension Education, 2021)
The challenge faced by the incubators in India is finding good start-ups that solve the problems in the market or in value chain. A well-structured incubation program may lead the startup from idea generation stage to setting up the business and most crucial funding support. Analysis of effectiveness of training programme was done using primary as well as secondary data. Progress report of the institute and primary information from the trainees were matched to reach usefulness of the training programme. The primary data was collected during August, 2019 to January 2020 with partial structured pre-scheduled interview. For the ICAR-BPD trainees there was no substantial variation in age or land ownership, implying that the comparison on certain dimensions could be due to the training programme rather than underlying human attributes. The ICAR-BPD trainees were mainly attempting to obtain government employment and were often unaware of the training and other resources available to help them establish their own enterprise. Almost all of the trainees attributed their progress to the RUDSET Institute’s EDP teaching.